Acupuncture therapy in postoperative rehabilitation for arthroscopic rotator cuff repair: a systematic review and meta-analysis - Chen, Jia-Hao; Wu, Kai; Wang, Qing-lai (Frontiers in Surgery, 2025)
IntroductionThis study aimed to evaluate the efficacy of acupuncture therapy in the postoperative rehabilitation of patients following arthroscopic rotator cuff repair.MethodsRandomized controlled trials (RCTs) published up to October 31, 2024, were identified through systematic searches of EMBASE, Web of Science, China National Knowledge Infrastructure, China Science and Technology Journal Database, China Biomedical Literature Database, and Wanfang Database. Meta-analysis was conducted using RevMan 5.3 and Stata 18. A total of 18 studies involving 376 patients were included.ResultsThe meta-analysis demonstrated that, compared to the control group, the acupuncture group showed significantly higher effective rates [OR = 5.02, 95% CI (2.32, 10.85), P < 0.001], improved Constant-Murley scores [MD = 7.27, 95% CI (3.96, 10.59), P < 0.001], greater range of motion in forward flexion [MD = 14.95, 95% CI (6.13, 23.77), P < 0.001], backward extension [MD = 6.58, 95% CI (3.56, 9.61), P < 0.001], abduction [MD = 16.24, 95% CI (6.79, 25.70), P < 0.001], external rotation [MD = 9.56, 95% CI (4.66, 14.47), P < 0.001], and significantly reduced pain according to Visual Analog Scale scores [MD = −1.45, 95% CI (−2.04, −0.86), P < 0.001].DiscussionAcupuncture therapy, when compared to conventional treatments, may be beneficial for postoperative rehabilitation in patients after arthroscopic rotator cuff repair by reducing pain and improving shoulder joint mobility.